Symbolic Rhetoric and Linguistic Hegemony: The Cultural Resonance of Serat Wedhatama in Suharto's Political Discourse - Suyitno; Supriyanto, Teguh; Nuryatin, Agus; Mardikantoro, Hari Bakti (Forum for Linguistic Studies, 2025)
In the postcolonial context, political language is often a tool for negotiating tradition and modernity, especially in Indonesia during the New Order era (1966–1998). The purpose of this research is to explore Serat Wedhatama, a 19th-century Javanese literary manuscript by Mangkunegara IV, which was adapted and represented in President Suharto's political rhetoric to strengthen the legitimacy of power. This research uses an interdisciplinary approach that combines Charles Sanders Peirce's semiotics, Antonio Gramsci's theory of cultural hegemony, and Norman Fairclough's critical discourse analysis (CDA). The focus of the research is also on the intertextuality between the Pangkur, Sinom, and Pucung pupuh in the three key speeches of Serat Wedhatama and Suharto. The results of the study show that Javanese idioms and metaphors, such as mikul dhuhur mendhem jero and legawa, are mobilized as symbolic representations to disguise political dominance and create the illusion of stability in the midst of a reform crisis. The rhetoric of harmony that emerged was not just the preservation of tradition, but a hegemonic strategy that leveraged cultural values for social consensus. These findings broaden the understanding of political language in postcolonial societies, confirming the strategic role of tradition in the reproduction of power. The implications of this study are practical for modern political communication in multicultural contexts, where cultural narratives can be used to reduce social polarization if supported by substantive actions.